Education For Children With Special Needs - Siahaan, Mander Kristian (The Explora, 2022)
Children have the right to experience an educational system. Education is a fundamental right for children, whether the child is healthy or has a health problem. When the medical problem of the child impairs him to learn in a normal school, it is necessary to find alternative forms of study. The fundamental children’s right for education is offered to children with special needs by special schools.This article aims to explain the importance of inclusive education for children with special needs. This statement is based on the fact that children with special needs do not receive proper education like other normal children. This paper opens an understanding and insight into the rights of every citizen, especially children with special needs, to obtain a proper education. To achieve this goal, the author uses a literature study. The literature study in question is that the author reads and records the results of the study of this topic from various library sources such as books, journals, and other key reports. The results of the study show that many parents and the community think that the implementation of inclusive education is too urgent for children with special needs. Therefore, children with special needs often get less attention and do not get the same education rights as normal children.